The generalist parasitoid Nasonia vitripennis shows more behavioural plasticity in host preference than its three specialist sister species. (8th August 2021) - Kalyanaraman, Dhevi; Gadau, Jürgen; Lammers, Mark
Abstract: Host preference is an important behaviour in parasitoid females as they must choose suitable hosts for their offspring. Preference includes location, recognition and acceptance of hosts. Both genetic and environmental factors can affect all those stages. Here, we focus on two factors (rearing history and experience) affecting host preference in the parasitoid wasp genus Nasonia (Hymenoptera: Chalcidoidea: Pteromalidae: Pteromalinae), which harbours both a host generalist ( N . vitripennis ) and several closely related specialists ( N . giraulti, N . longicornis and N . oneida ). We tested whether Nasonia females prefer the host that they developed in by rearing them on two different host species ( Lucilia sericata and Calliphora vomitoria ) for over 10 generations before testing them for their host preference. We then tested whether experience changes host preference by allowing the females to feed and oviposit on either host species before testing their host preference. Only the generalist N . vitripennis showed behavioural plasticity as the effect of rearing history on host preference was overruled by their experience with a different host species. In contrast, the three specialist species were not affected by long‐term rearing history and only shifted their host preference based on experience. In all four known Nasonia species, individual adult experience modulated host recognition, acceptance and preference.